Kinematic differences in the snatch lift according to increased loads in elite female weightlifters - Gil, H.; Park, T.; Yeom, D.; Kim, D.; Ryu, S. (Korean Journal of Sport Biomechanics, 2025)
Objective: This study aimed to investigate the effects of increasing load (75%, 80%, 85% of one-repetition maximum [1RM]) on postural stability and joint kinematics during the Snatch lift in elite collegiate female weightlifters. Method: Fifteen female weightlifters participated (Age: 20.3 ± 1.2 yr, Height: 162.0 ± 4.9 cm, Body Mass: 73.7 ± 16.9 kg). Each athlete performed two Snatch trials at 75%, 80%, and 85% of her 1RM. Three-dimensional kinematic data were obtained using the Theia3D markerless system. Horizontal displacement among the base of support (BOS), center of mass (COM), and barbell; trunk segment angles; and hip, knee, and ankle joint angles and ranges of motion (ROM) were analyzed across five events (E1-E5) and four phases (P1-P4). A repeated-measures ANOVA was conducted (a = .05). Results: Horizontal displacement between BOS-COM and BOS-bar showed no differences from E1 to E4, but was significantly greater at E5 under the 85% condition compared with 80% (p<.05). Trunk extension angles were higher at E3 and E4 under heavier loads (85%>80% >75%, p<.05). ROM increased during the second pull (P2) and catch phase (P4), whereas ROM during the turnover phase (P3) was reduced with higher loads. Lower-limb joints exhibited similar patterns: hip, knee, and ankle ROM decreased at P3 but increased at P4 under the 85% load (p<.05). Conclusion: Female lifters maintained stable COM-bar alignment across load conditions; however, increasing load elicited compensatory adjustments characterized by restricted ROM during the turnover phase and greater ROM during the pull and catch phases. These findings suggest that load-induced instability in female lifters is influenced more by phase-specific ROM allocation and control strategies than by simple strength limitations.